A broader perspective on the causes and consequences of eastern Australia's 2019–20 season of mega‐fires: A response to Adams et al. (28th May 2020) - Bradstock, Ross A.; Nolan, Rachael H.; Collins, Luke; Resco de Dios, Víctor; Clarke, Hamish; Jenkins, Meaghan; Kenny, Belinda; Boer, Matthias M.
Abstract : This article is a Response to Adams et al . 26, 3756–3758 . See also the Letter by Nolan et al . 26, 1039–1041 .